Atlantic Salmon Recovery Informing and Informed by Ecosystem‐Based Fisheries Management. Issue 9 (25th March 2019) - Hare, Jonathan A.; Kocik, John F.; Link, Jason S.
Abstract : 2019 is the International Year of the Salmon with events and projects planned across the Northern Hemisphere. Obviously, much of the focus will be on salmon. Yet, we contend in this perspective that salmon recovery, specifically Atlantic Salmon Salmo salar recovery, can inform and be informed by Ecosystem Based Fisheries Management (EBFM). We provide the status of Atlantic Salmon recovery and the definition and objectives of EBFM and then walk through Atlantic Salmon recovery in the context of the definition of EBFM. Our purpose is to provide insight into EBFM in practice. Then we use the principles of EBFM to examine Atlantic Salmon recovery and provide an ecosystem perspective of the recovery efforts. Our intent is to provide a practical approach to considering EBFM and a broader approach for considering Atlantic Salmon recovery.